2020
DOI: 10.7717/peerj.9386
|View full text |Cite
|
Sign up to set email alerts
|

Variation of soil nutrients and bacterial community diversity of different land utilization types in Yangtze River Basin, Chongqing Municipality

Abstract: The diversity and community distribution of soil bacteria in different land use types in Yangtze River Basin, Chongqing Municipality were studied by using Illumina MiSeq analysis methods. Soil physical and chemical properties were determined, and correlation analyses were performed to identify the key factors affecting bacterial numbers and α-diversity in these soils. The results showed that the soil physical and chemical properties of different land use types decrease in the order: mixed forest (M2) > pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The potential main hosts of ARGs in the Ili River were Proteobacteria, Bacteroidetes, and Actinobacteria, which is consistent with other findings in the Yellow River Delta, Chongqing municipality, and the Karst River (Li et al, 2020;Xiang et al, 2020); however, the distribution of ARGs was different in different studies. It is reported that human activity promoted the spread of sulfonamide and tetracycline resistance genes in many rivers like the Yangtze River, Liaohe River, and the northern Yellow Sea, while this study found the fluoroquinolone, tetracycline, and aminoglycoside resistance genes as the most abundant ARGs.…”
Section: Discussionsupporting
confidence: 89%
“…The potential main hosts of ARGs in the Ili River were Proteobacteria, Bacteroidetes, and Actinobacteria, which is consistent with other findings in the Yellow River Delta, Chongqing municipality, and the Karst River (Li et al, 2020;Xiang et al, 2020); however, the distribution of ARGs was different in different studies. It is reported that human activity promoted the spread of sulfonamide and tetracycline resistance genes in many rivers like the Yangtze River, Liaohe River, and the northern Yellow Sea, while this study found the fluoroquinolone, tetracycline, and aminoglycoside resistance genes as the most abundant ARGs.…”
Section: Discussionsupporting
confidence: 89%
“…Some likely sources of ARGs in Kuwait's marine environment could be the chronic metal discharges from the shipping industry, desalination plants, and airborne input with dust, in addition to the pharmaceuticals introduced through wastewater discharges. The AMR is also reported in the Yellow River Delta [54], Yangtze river basin [55], Karst River [56], Xisha Island [49], and Ili River [57]. Proteobacteria (46%), Bacteroidetes (10%), and Actinobacteria (5%) were the main hosts of ARGs in the Kuwait coastal area.…”
Section: Discussionmentioning
confidence: 74%
“…The majority were resistant to the beta-lactams, cephalosporins (102), and penam (102). In addition, ARGs resistant to tetracycline (93), aminoglycoside (63), fluoroquinolone (55), carbapenem (48), lincosamide (40), cephamycin (35), phenicol (34), streptogramin (34), peptide antibiotics (29), and monobactum (28) were also recorded (Figure 6). A total of 25 or fewer ARGs were resistant to the drug classes of the glycopeptide, aminocoumarin, diaminopyrimidine, penem, rifamycin, glycylcycline, acridine dye, triclosan, pleuromutilin, sulfonamide, fos-fomycin, nucleoside antibiotic, oxazolidinone, fusidic acid, mupirocin, sulfone, elfamycin, nitroimidazole, antibacterial free fatty acid antibiotics, and nitrofuran.…”
Section: Args Against Drug Classesmentioning
confidence: 99%
“…Li [15] and Lai [34] showed that different forest types have a significant impact on soil properties, such as soil's physical and chemical properties. Different forest types lead to certain differences in surface litter reserves and their composition, tree root growth and development, and the litter decomposition rate, resulting in different physical properties of the soil of different forest stands [35].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, higher plant diversity may produce a higher biochemical diversity of root exudates, which further increases the soil's organic matter content [14]. Soil is an important part of the forest ecosystem and plays an important role in maintaining the stability of the terrestrial ecosystem, material circulation, and energy conversion [15]. Soil is also the foundation of plant growth and development.…”
Section: Introductionmentioning
confidence: 99%